2010
DOI: 10.1900/rds.2010.7.36
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Homeostasis in Pre-diabetic NOD and Lymphocyte-Deficient NOD/SCID Mice During Gestation

Abstract: ■ AbstractBACKGROUND: Unlike other strains, spontaneously type 1 non-obese diabetic (NOD) mice experience transient hyperinsulinemia after weaning. The same applies for NOD/SCID mice, which lack functional lymphocytes, and unlike NOD mice, do not develop insulitis and diabetes like NOD mice. AIMS: Given that β-cell stimulation is a natural feature of gestation, we hypothesized that glucose homeostasis is disturbed in gestate pre-diabetic NOD and non-diabetic NOD/SCID mice, which may accelerate the onset of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
(90 reference statements)
2
3
0
Order By: Relevance
“…8). We found that the level of insulin expression was statistically indistinguishable between NOD.HLA-B*39:06 Hom .β2m KO mice and their Ins2 Het and Ins2 KO counterparts, with an average concentration of 0.8 ng/ml, consistent with previous reports for other mouse strains (44). This supports the notion that the changes in disease onset are due to diminished immunological tolerance to insulin (30, 31) and not to an inherently decreased ability to produce insulin.…”
Section: Resultssupporting
confidence: 91%
“…8). We found that the level of insulin expression was statistically indistinguishable between NOD.HLA-B*39:06 Hom .β2m KO mice and their Ins2 Het and Ins2 KO counterparts, with an average concentration of 0.8 ng/ml, consistent with previous reports for other mouse strains (44). This supports the notion that the changes in disease onset are due to diminished immunological tolerance to insulin (30, 31) and not to an inherently decreased ability to produce insulin.…”
Section: Resultssupporting
confidence: 91%
“…9). We found that the level of insulin expression was statistically indistinguishable between NOD.HLA-B*39:06 Hom .β2m KO mice and their Ins2 Het and Ins2 KO counterparts, with an average concentration of 0.8 ng/ml, consistent with previous reports for other mouse strains (37, 47). This supports the notion that the changes in disease onset are solely due to diminished T cell tolerance to insulin associated with Ins2 ablation (2830, 32), and not also influenced by an inherently decreased ability to produce insulin.…”
Section: Resultssupporting
confidence: 91%
“…Steroid hormones have been shown to counteract the mitogenic, prosurvival, and functional effects of PRL/PL in β-cells in vitro ( 31 , 32 , 50 ), suggesting that upregulation of steroid hormones at the end of pregnancy could be responsible for the increase in β-cell death and normalization of β-cell mass and function. In our studies, we have found that the absence of HGF/c-Met signaling in β-cells leads to increased β-cell death at GD15, when β-cell death is not altered in wild-type mice, suggesting enhanced sensitivity to mild increases in steroid hormone levels that could occur at this gestational day ( 51 , 52 ). Indeed, PancMet KO β-cells are more sensitive than wild-type cells to death induced by low doses of dexamethasone, and HGF protects human β-cells from dexamethasone-induced cell death in vitro, further reinforcing the possibility that c-Met deficiency might enhance the susceptibility of β-cells to the negative effects of mild hormonal changes ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 60%